A tandem mass spectrometry-based method to assess the architectural purity of synthetic polymers: a case of a cyclic polylactide obtained by click chemistry. Issue 1 (23rd September 2014) - Josse, Thomas; De Winter, Julien; Dubois, Philippe; Coulembier, Olivier; Gerbaux, Pascal; Memboeuf, Antony
Abstract : A tandem mass spectrometry-based method is developed to determine the degree of purity achieved in the cyclization of a linear poly(l -lactide). Abstract : A tandem mass spectrometry-based method is developed to determine the degree of purity achieved in the cyclization of a linear poly(l -lactide) prepared by copper-catalyzed alkyne-azide cycloaddition. When proton nuclear magnetic resonance, size-exclusion chromatography, and single-stage mass spectrometry are unable to demonstrate the presence of a residual linear polymer, the proposed ESI-tandem mass spectrometry methodology allows detection of starting material traces (<5%) based on radically different collision-induced dissociation (CID) behaviours. The technique is believed to be readily adaptable to numerous isomeric pairs of macromolecules presenting different CID characteristics.